Pengaruh Self Efficacy, Individual innovation capabillity dan Knowledge sharing terhadap Kinerja karyawan di Industri tas. - Darmarini, Aulia Rahma; Sumartik, Sumartik; Firdaus, Vera (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This research aims to determine the influence of self-efficacy, individual innovation capability and knowledge sharing on employee performance. This research uses quantitative methods with total sampling of Ud employees. Surwalandono to evaluate the influence of self-efficacy, individual innovation capability, and knowledge sharing on employee performance in the bag industry. Data analysis used multiple linear regression with SPSS. The research results show that there is an influence between the variables self efficacy, individual innovation capability and knowledge sharing which is positive and significant. The self-efficacy variable has a positive and significant effect on employee performance. Individual innovation capability has a positive and significant effect on employee performance. Knowledge sharing has a positive and significant effect on employee performance.